Open multimodal iEEG-fMRI dataset from naturalistic stimulation with a short audiovisual film - Julia Berezutskaya; Mariska J. Vansteensel; Erik J. Aarnoutse; Zachary V. Freudenburg; Giovanni Piantoni; Mariana P. Branco; Nick F. Ramsey (Scientific Data, 2022)
Measurement(s) brain activity measurement Technology Type(s) Intracranial EEG • functional magnetic resonance imaging Factor Type(s) Short audiovisual film stimulus Sample Characteristic - Organism Homo sapiens